Hubungan Komunikasi Terapeutik Terhadap Kepuasan Pasien Pelayanan Kesehatan Gigi dan Mulut di Klinik Gigi. - Siti Adlinah Fatman; Badai Septa Wahyudadi; Jumriani Jumriani; Ira Liasari Ira Liasari; Nurfialsa Aprilia (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2026)
Therapeutic communication is an essential aspect of dental and oral health services because it can influence patients’ perceptions and satisfaction with the care they receive. This study aimed to determine the relationship between therapeutic communication and patient satisfaction in dental and oral health services at Trisya Medika Dental Clinic, Bone Regency. This study employed an analytical observational design with a cross-sectional approach. The study population consisted of patients receiving dental and oral health treatment at Trisya Medika Dental Clinic. Samples were selected using an accidental sampling technique, resulting in 51 respondents. Data were collected using therapeutic communication and patient satisfaction questionnaires. Data analysis included univariate and bivariate analyses. The findings indicated that therapeutic communication practiced by dental health professionals was associated with patient satisfaction. Patients who perceived better therapeutic communication tended to report higher levels of satisfaction with the dental and oral health services they received. Effective therapeutic communication through clear information delivery, empathetic attitudes, and active listening to patients’ concerns contributed to creating a positive healthcare experience. It can be concluded that therapeutic communication is one of the factors associated with patient satisfaction in dental and oral health services at Trisya Medika Dental Clinic, Bone Regency.